Information Technology Governance Audit Using COBIT 5 Framework in the Natural Resources Conservation Office - I Gede Eka Artha Putra; Luh Joni Erawati Dewi; I Made Gede Sunarya (Information Technology and Science (ITScience), 2023)
One of the organizations that requires the implementation of good information technology governance is the natural resources conservation office. The audit was conducted to determine the level of IT process capability based on the COBIT 5 standard and to determine the level of gaps (gaps) owned by the natural resources conservation office. The process of implementing the audit begins with observing the agency's environment related to activity data and its implementation, then mapping the data with business objectives according to COBIT 5, followed by mapping business objectives with IT objectives to obtain IT processes. The IT processes obtained are then selected to obtain important IT processes according to company officials. The TI process obtained is then processed using the Guttman method. The results of the IT process capability level, namely EDM01, EDM02 and APO09, are at level 3 (established). The gaps found need to be given a corrective strategy to achieve the capability expected by the institution, namely 4 (predictable process) by providing recommendations regarding steps to achieve the expected capability value. The recommendations and improvements provided use ISO/IEC 15504:2 and ISO27002 standards which were obtained by mapping IT processes on COBIT 5.